2019
DOI: 10.3389/fneur.2019.00269
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy for Acute Ischemic Stroke of Intracranial Atherosclerotic Origin—Neuroimaging Perspectives

Abstract: Large vessel occlusion (LVO) due to intracranial atherosclerosis (ICAS) is a common cause of acute ischemic stroke (AIS) in Asians. Endovascular therapy (EVT) has been established as the mainstay of treatment in patients with AIS and LVO. However, only a few patients of Asian descent with ICAS-related LVO (ICAS-LVO) were included in recent randomized controlled trials of EVT for AIS. Therefore, the findings of these trials cannot be directly applied to Asian patients with ICAS-LVO. In embolic LVO due to thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Many patients considered ICAS were treated with balloon dilatation or stent implantation directly instead of stent thrombectomy. In our study, univariate analysis showed that patients with DR had significantly higher frequencies of ICAS (94.1% vs. 61.8%; P = 0.01) and intracranial angioplasty (88.2% vs. 57.2%; P = 0.02) and most of these patients were treated with balloon dilatation or stent first which can damage the fibrous cap and lead to aggravation of in situ reocclusion [ 22 , 23 ]. Our further analysis showed that there was no significance related to in patients treated with remedial measures after stent thrombectomy.…”
Section: Discussionmentioning
confidence: 93%
“…Many patients considered ICAS were treated with balloon dilatation or stent implantation directly instead of stent thrombectomy. In our study, univariate analysis showed that patients with DR had significantly higher frequencies of ICAS (94.1% vs. 61.8%; P = 0.01) and intracranial angioplasty (88.2% vs. 57.2%; P = 0.02) and most of these patients were treated with balloon dilatation or stent first which can damage the fibrous cap and lead to aggravation of in situ reocclusion [ 22 , 23 ]. Our further analysis showed that there was no significance related to in patients treated with remedial measures after stent thrombectomy.…”
Section: Discussionmentioning
confidence: 93%
“…21,22 The differential diagnosis for ICAD-LVO includes vasospasm, dissection, and residual embolus. 8,23,24 Vasospasm is characterized by a transient focal narrowing in the arterial lumen which may improve with intraarterial vasodilators, such as verapamil or nicardipine. 25,26 Intracranial dissection, which can be iatrogenic, traumatic, or spontaneous, is recognized when a dissection flap is visualized.…”
Section: Intraprocedural Identification Of Icad-lvomentioning
confidence: 99%
“…Additionally, OCT can provide good-quality imaging of vessel wall layers to identify patients with ICAD-LVO. 56…”
Section: Dsa Intravascular Ultrasound and Optical Coherence Tomographymentioning
confidence: 99%
“…Additionally, OCT can provide good-quality imaging of vessel wall layers to identify patients with ICAD-LVO. 56 In summary, early prediction of ICAD-LVO prior to an endovascular procedure is challenging. An integration of baseline clinical history, vascular risk factors, and imaging indicators can increase the accuracy of ICAD-LVO prediction.…”
Section: Dsa Intravascular Ultrasound and Optical Coherence Tomographymentioning
confidence: 99%